Hepatitis E Virus (HEV): Identification of Subtypes 3b and 3m in Wild Boar Population in Liguria Region, Italy - Roberta Battistini; Laura Serracca; Elisabetta Razzuoli; Valeria Listorti; Lisa Guardone; Monica Dellepiane; Nicola Pussini; Francesco Brunelli; Simone Peletto; Chiara Beltramo; Carlo Ercolini; Chiara Masotti (Pathogens, 2022)
The wild boar is an important natural reservoir for the zoonotic transmission of the hepatitis E virus (HEV) around the world. In particular, HEV genotypes 3 and 4 are an emerging problem in industrialized countries, as the number of wild boars has increased, and their territory is ever closer to farms and populated areas. This study describes the HEV prevalence and geographic circulation among wild boar populations in the Ligurian region (Italy) during the period 2019–2022. Liver samples from 849 wild boars were analyzed for HEV RNA using real-time RT-PCR; positive samples were then subjected to sequencing and phylogenetic analysis. Overall, 6.7% of the wild boars were positive for HEV RNA; however, in the last two years, the percentage of positive animals almost doubled. Phylogenetic analysis showed that wild boar HEV sequences belonged to genotype 3 and clustered within subtypes 3a and 3c, and, for the first time in Italy, subtypes 3b and 3m were identified. Interestingly, 13 sequences could not be assigned to a recognized subtype. Furthermore, the results showed different circulations of identified subtypes across the territory. These findings increase the knowledge of HEV-3 heterogeneity in Italy and describe the role of wild boars in maintaining an active viral circulation in the environment.